Long QT syndrome followed by torasades de pointes due to fluconazole in remission induction chemotherapy for acute myelogenous leukemia - Fujimoto, Yoshinori; Umeda, Masanori; Ishihara, Susumu; Nagase, Daisuke; Arai, Chiaki; Kuraishi, Yasunobu; Sugasawa, Yasuyuki; Kato, Motohiro; Natori, Kazuhiko; Izumi, Haruka; Okuda, Shinya (Japanese Journal of Chemotherapy, 2005)
A 48-year-old man diagnosed with acute myeloid leukemia in November 1999 and undergoing bone marrow suppression after remission induction chemotherapy suffered fungal pneumonia treated with anti fungal fluconazole (FLCZ). On day 14 of the anti fungal treatment, he suffering from torsades de points, evidenced by a typical ECG pattern sign curve, was compatible with torasades de points. He felt palpitations and unclear conciousness and we found prolonged QT time on ECG and low serum Ca, grtimenormalized when was FLCZ discontinued and was serum Ca was corrected. This very rare disorder is potentially fatal, and long QT time syndrome should be considered in pastients being treated with FLCZ for fungal infection.